Dominant Role of Atlantic Multidecadal Oscillation in the Recent Decadal Changes in Western North Pacific Tropical Cyclone Activity. Issue 1 (11th January 2018) - Zhang, Wei; Vecchi, Gabriel A.; Murakami, Hiroyuki; Villarini, Gabriele; Delworth, Thomas L.; Yang, Xiaosong; Jia, Liwei
Abstract: Over the 1997–2014 period, the mean frequency of western North Pacific (WNP) tropical cyclones (TCs) was markedly lower ( 18%) than the period 1980–1996. Here we show that these changes were driven by an intensification of the vertical wind shear in the southeastern/eastern WNP tied to the changes in the Walker circulation, which arose primarily in response to the enhanced sea surface temperature (SST) warming in the North Atlantic, while the SST anomalies associated with the negative phase of the Pacific Decadal Oscillation in the tropical Pacific and the anthropogenic forcing play only secondary roles. These results are based on observations and experiments using the Geophysical Fluid Dynamics Laboratory Forecast‐oriented Low‐ocean Resolution Coupled Climate Model coupled climate model. The present study suggests a crucial role of the North Atlantic SST in causing decadal changes to WNP TC frequency. Plain Language Summary: The western North Pacific (WNP) is the most active ocean basin for tropical cyclone (TC) activity, with very significant societal and economic impacts. Over 1997–2014, the number of WNP TCs has abruptly decreased ( 18%). We examine the relative roles of sea surface temperature (SST) changes and anthropogenic forcing in this decrease of WNP TCs. This change of WNP TCs is driven by an intensification of the vertical wind shear in the southeastern/eastern WNP which is mainly tied to SST warming in the North Atlantic, while the SST anomalies associated with the negative Pacific Decadal Oscillation phase and the anthropogenic forcing only play secondary roles. The present study suggests a crucial role of the North Atlantic SST in causing the observed decadal change in WNP TC frequency. Key Points: The recent decrease in WNP TCs was driven by an intensification of vertical wind shear in the southeastern/eastern WNP The intensified vertical wind shear in the southeastern/eastern WNP arose primarily from the enhanced SST warming in the North Atlantic The SST anomalies in the tropical Pacific associated with the negative PDO and the anthropogenic forcing play only secondary roles